Comparison of Change in Peritoneal Function in Patients on Continuous Ambulatory PD vs Automated PD. Issue 6 (November 2017) - Samad, Nasreen; Fan, Stanley L.
Background: Patients on automated peritoneal dialysis (APD) may have greater exposure to glucose in the PD fluid than those on continuous ambulatory PD (CAPD). If this causes long-term damage to the peritoneal membrane, it will have implications for a patient's choice of modality. Methods: Membrane function of long-term APD or CAPD patients was followed prospectively. The data were collected from electronic patient records in our unit from 2000 to 2014. The rate of change in membrane transport status (D/Pcr) and ultrafiltration (UF4 ) for each patient was calculated using the least square regression line equation. Results: We identified 106 APD and 123 CAPD patients who had a mean of 8.4 peritoneal equilibration test (PET) over 5.6 years. No differences were found in the rate of changes in D/Pcr or UF4 . Baseline solute clearance (Kt/V) was lower in APD patients (1.66 vs 1.76, p = 0.04). However, APD patients experienced incremental changes to dialysis prescription that resulted in a greater increase in Kt/V compared with CAPD patients. Conclusion: This is the largest study comparing the long-term effect of APD vs CAPD prescriptions. Despite more glucose being prescribed, there were no differences in the evolution of peritoneal membrane transport characteristics. The lower baseline Kt/V of APD patients might be explained by our aggressive use of incremental APD (tidal with dry day). Despite greater glucose prescriptions, initiating patients on APD based on patient preference appears to be safe for the long-term integrity of the peritoneal membrane.